2022
DOI: 10.1021/acssuschemeng.2c01983
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Environmental Barriers of CO2-Based Fischer–Tropsch Electro-Diesel

Abstract: Electro-fuels are seen as a promising alternative to curb carbon emissions in the transport sector due to their appealing properties, similar to those of their fossil counterparts, allowing them to use current infrastructure and state-of-the-art automotive technologies. However, their broad implications beyond climate change remain unclear as previous studies mainly focused on analyzing their carbon footprint. To fill this gap, here, we evaluated the environmental and economic impact of Fischer–Tropsch electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…311 The production of e-diesel in an electrically driven FT process will substantially reduce its global warming impact but the total environmental impacts of the two processes need to be compared for a complete evaluation (caveat emptor). 312 Replacing energy intensive steam crackers, that use gas-fired furnaces and generate huge amounts of carbon dioxide, by electric cracking of hydrocarbons using renewable electricity is also a possibility. 313 Electrolytic reduction of carbon dioxide can be utilised to produce methanol as a high-energy-density liquid fuel and raw material for commodity chemicals manufacture, in a methanol economy as envisaged by Olah and co-workers.…”
Section: The Energy Transition and Beyond: Decarbonisation Of Energy ...mentioning
confidence: 99%
See 1 more Smart Citation
“…311 The production of e-diesel in an electrically driven FT process will substantially reduce its global warming impact but the total environmental impacts of the two processes need to be compared for a complete evaluation (caveat emptor). 312 Replacing energy intensive steam crackers, that use gas-fired furnaces and generate huge amounts of carbon dioxide, by electric cracking of hydrocarbons using renewable electricity is also a possibility. 313 Electrolytic reduction of carbon dioxide can be utilised to produce methanol as a high-energy-density liquid fuel and raw material for commodity chemicals manufacture, in a methanol economy as envisaged by Olah and co-workers.…”
Section: The Energy Transition and Beyond: Decarbonisation Of Energy ...mentioning
confidence: 99%
“…311 The production of e-diesel in an electrically driven FT process will substantially reduce its global warming impact but the total environmental impacts of the two processes need to be compared for a complete evaluation (caveat emptor). 312 Replacing energy intensive steam crackers, that use gas-fired furnaces and generate huge amounts of carbon dioxide, by electric cracking of hydrocarbons using renewable electricity is also a possibility. 313…”
Section: The Energy Transition and Beyond: Decarbonisation Of Energy ...mentioning
confidence: 99%
“…Electricity-based fuels (e-fuels), for instance, can reduce GWI substantially compared to fossil fuels if produced from renewable electricity and carbon sources, at the cost of increases in other impact categories, e.g., resource use of minerals and metals. 22,23 In contrast, biomass-based fuels (biofuels), e.g., ethanol, are known to increase agricultural land occupation substantially compared to their fossil-based counterparts. 24 Therefore, a holistic design approach should cover a wide range of impact categories as additional objectives to quantify and avoid potential burden-shiing.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, for the plasma process to be competitive, the removal of O 2 is necessary to deliver an industrially relevant gas mixture for the production of synthetic fuels, e.g., via the Fischer−Tropsch process. 11 One sensitivity analysis study has shown that gas separation would be the dominant cost factor in a plasmabased CO 2 -to-CO chemical plant. 12 Strategies/technologies that have been proposed to process the outlet mixture of a plasma reactor to produce O 2 -free streams include the use of sacrificial materials such as biochar that consume the produced O 2 , 13 zeolites that selectively remove CO 2 and CO from the gas stream 14 and mixed ionic-electronic conductors (MIECs) as standalone membranes or ion conductors incorporated in electrochemical cells for oxygen removal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The outlet gas mixture of plasma-based conversion technology consists typically of CO 2 , CO, and O 2 , which contrasts with the O 2 -free streams produced by electrolysis cells . Thus, for the plasma process to be competitive, the removal of O 2 is necessary to deliver an industrially relevant gas mixture for the production of synthetic fuels, e.g., via the Fischer–Tropsch process . One sensitivity analysis study has shown that gas separation would be the dominant cost factor in a plasma-based CO 2 -to-CO chemical plant .…”
Section: Introductionmentioning
confidence: 99%